Managing customer retention in Etiqa Takaful Khiron’s Agency Group: a manifestation of theory and practices / Nur Arfah Mustapha - Mustapha, Nur Arfah (2010)
This research investigated the customer retention management in this organization compared to the theory of Customer Relationship Management (CRM), with particularly focus on the customer satisfaction by doing marketing programs and recruiting the right people.